(untitled) (Bangladesh Journal of Child Health, 2012)
Kasabach Merritt syndrome (KMS) is an uncommon complication of large haemangioma in which there is thrombocytopenia and coagulopathy. We report a case of a new born male baby presented with a large haemangioma on the right upper extremity and his initial laboratory tests were consistent with consumptive coagulopathy. He was diagnosed as a case of KMS and treated with oral prednisolone. DOI: http://dx.doi.org/10.3329/bjch.v36i2.13091 Bangladesh J Child Health 2012; Vol 36 (2): 105-107